Dreaming furiously? – A sleep laboratory study on the dream content of people with parkinson's disease and with or without rapid eye movement sleep behavior disorder - Valli K.; Frauscher B.; Peltomaa T.; Gschliesser V.; Revonsuo A.; Högl B. (Elsevier, 2022)
Objective: Rapid eye movement (REM) sleep behavior disorder (RBD) has been related to altered, action-filled, vivid, and aggressive dream content, but research comparing the possible differences in dreams of Parkinson's disease (PD) patients with and without RBD is scarce. The dream content of PD patients with and without RBD was analyzed with specific focus on action-filledness, vividness, emotional valence, and threats. Methods: A total of 69 REM and NREM dream reports were collected in the sleep laboratory, 37 from nine PD patients with RBD and 32 from six PD patients without RBD. A content analysis of (1) action-filledness (actions and environmental events); (2) vividness (emotions and cognitive activity); (3) intensity of actions, events and emotions; (4) emotional valence, and (5) threatening events was performed on the transcripts. Results: Altogether 563 dream elements expressing action-filledness and vividness were found. There were no significant between-group differences in the number or distribution of elements reflecting action-filledness or vividness, emotional valence or threats. In within-group analyses, PD patients with RBD had significantly more negative compared to positive dreams (p = 0.012) and compared to PD patients without RBD, a tendency to have more intense actions in their dreams (p = 0.066). Conclusions: Based on the results of this study, there are no major between-group differences in the action-filledness, vividness, or threat content of dreams of PD patients with and without RBD. However, within-group analyses revealed that dreams were more often negatively than positively toned in PD patients with RBD.